ANTECEDENTS OF RETAILER TRUST ON SUPPLIER TO CREATE LONG TERM RELATIONSHIP - Sulistyorini, Ery; Irawanto, Dodi Wirawan; Rahayu, Mintarti (Universitas Brawijaya, Indonesia, 2018)
This research aims to reveal the role of communication, satisfaction, and commitment as the antecedents of trust; also, this research observes the role of trust in the long-term relationship.Data collection is done through questionnaire distribution. The questionnaire is sent to 80 owners/managers of laptop retail stores in Malang city. The respondents are chosen using purposive sampling technique. Data analysis technique this research using path analysis. The result indicates that communication, satisfaction, and commitment influence trust; next, trust affects the long-term relationship. Communication has the most significant effect on trust compared to commitment and satisfaction. This finding is expected to be able to help the retailers in maintaining the long-term relationship with their supplier by considering the relationship between trust and communication as well as satisfaction and commitment with their supplier.